The bounds of reason game theory and the unification of the behavioral sciences - Gintis, Herbert 1940-2023 (Princeton Univ. Press, 2009)
Game theory cannot fully explain human behaviour and should instead complement other key concepts championed by the behavioral disciplines. Gintis shows that just as game theory without broader social theory is merely technical bravado, so social theory without game theory is a handicapped enterprise.